1993
DOI: 10.1159/000457535
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound Assessment of the Effects of Ketamine on Neonatal Cerebral Circulation

Abstract: The effects of a single dose of 5 mg-kg-(1) of ketamine administered intravenously to 10 critically ill preterm infants prior to epicutaneo-caval catheterization were analyzed using pulsedwave Doppler ultrasound. The infants weighed between 670 and 1,885 g and their gestational ages ranged from 26 to 33 weeks. Arterial pressure (MAP), cardiac output (CO), transcutaneous oxygen pressure (TCPO(2)), transcutaneous carbon dioxide pressure (TCPCO(2)), end-diastolic velocity (EDV), peak systolic velocity (PSV), mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The heart rate decreased only after administration of 2 mg/kg ketamine, and there were no statistically or clinically significant changes in blood pressure after any doses of ketamine. In a previous study, in which 10 preterm infants, aged 1–10 days, received 5 mg/kg ketamine intravenously before central venous catheterisation, a significant but short lasting decrease in arterial blood pressure was observed two minutes after ketamine administration, but no changes in cerebral blood flow occurred 9. A moderate decrease in arterial blood pressure was also observed in another study in which 20 2 week old preterm infants received 2 mg/kg ketamine intravenously before surgical procedures 19.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The heart rate decreased only after administration of 2 mg/kg ketamine, and there were no statistically or clinically significant changes in blood pressure after any doses of ketamine. In a previous study, in which 10 preterm infants, aged 1–10 days, received 5 mg/kg ketamine intravenously before central venous catheterisation, a significant but short lasting decrease in arterial blood pressure was observed two minutes after ketamine administration, but no changes in cerebral blood flow occurred 9. A moderate decrease in arterial blood pressure was also observed in another study in which 20 2 week old preterm infants received 2 mg/kg ketamine intravenously before surgical procedures 19.…”
Section: Discussionmentioning
confidence: 84%
“…As only a few studies have been carried out on the analgesic use of ketamine during the neonatal period,8 9 we designed this randomised trial to evaluate its suitability and the appropriate dose for relief of the brief discomfort and pain caused by tracheal suction in newborn infants during the recovery period of ventilator treatment when sedation or analgesia is usually avoided.…”
mentioning
confidence: 99%
“…Systemic and cerebral hemodynamic effects of ketamine were assessed when used as analgesic therapy for central vein catheterization. No impairment of hemodynamics could be shown (124). When used for short procedures, higher doses of ketamine (2 mg/kg) reduced heart rate (125) and 5 mg/kg reduced blood pressure without impairing cardiac output (124).…”
Section: Existing Human Data On Neurotoxicity Of Sedative Drugs Used mentioning
confidence: 99%
“…No impairment of hemodynamics could be shown (124). When used for short procedures, higher doses of ketamine (2 mg/kg) reduced heart rate (125) and 5 mg/kg reduced blood pressure without impairing cardiac output (124). Studies of infants undergoing cardiac catheterization have reported respiratory complications (126) and increased blood pressure (127).…”
Section: Existing Human Data On Neurotoxicity Of Sedative Drugs Used mentioning
confidence: 99%
See 1 more Smart Citation